The Effectiveness of Capital Adequacy Measures in Predicting Bank Distress - David G. Mayes; Hanno Stremmel (SUERF - The European Money and Finance Forum, 2014)
Our concern in this paper is two-fold: first to see whether the determinants of bank distress and failure have been any different in the GFC from previous years: second to see whether simple measures of capital adequacy outperform their risk-weighted counterparts as predictors, despite the focus on the later in the Basel framework. This paper examines bank distress within a large quarterly data set of FDIC-insured US banks from 1992 to 2012. We contrast the effects of risk-weighted and non-risk-weighted capital measures for various banking types using two estimation methods (logit and discrete survival time analysis). We predict bank failures and draw inferences about the stability of contributing bank characteristics. Our models incorporate CAMELS indicators that consider the bank-specific variables and macroeconomic conditions. We find that the non-risk-weighted capital measure, the adjusted leverage ratio, explains bank distress and failures best with considerable accuracy. Further, we find that the influence of the characteristics in the two methods differs only slightly. Also the characteristics of banks getting into bank distress are alike over time. That means that the familiar banking characteristics for identifying a distress-prone bank identified fragile banks effectively during the global crisis without new information and are likely to continue to work well in the future. Further, our findings suggest that the more complex a bank is the more effective is the leverage ratio compared to the risk-based capital ratio
Keywords: G01; G21; G28; G33; 330; Bank Failure; Basel III; CAMELS; Early Warning System; Leverage Ratio; Risk-Based Capital; Regulation; Bankrisiko; Bankenliquidität; Bankenregulierung; USA